First-line rituximab combined with short-term prednisone versus prednisone alone for the treatment of pemphigus (Ritux 3): a prospective, multicentre, parallel-group, open-label randomised trial. Issue 10083 (20th May 2017) - Joly, Pascal; Maho-Vaillant, Maud; Prost-Squarcioni, Catherine; Hebert, Vivien; Houivet, Estelle; Calbo, Sébastien; Caillot, Frédérique; Golinski, Marie Laure; Labeille, Bruno; Picard-Dahan, Catherine; Paul, Carle; Richard, Marie-Aleth; et al.
Summary: Background: High doses of corticosteroids are considered the standard treatment for pemphigus. Because long-term corticosteroid treatment can cause severe and even life-threatening side-effects in patients with this disease, we assessed whether first-line use of rituximab as adjuvant therapy could improve the proportion of patients achieving complete remission off-therapy, compared with corticosteroid treatment alone, while decreasing treatment side-effects of corticosteroids. Methods: We did a prospective, multicentre, parallel-group, open-label, randomised trial in 25 dermatology hospital departments in France (Ritux 3). Eligible participants were patients with newly diagnosed pemphigus aged 18–80 years being treated for the first time (not at the time of a relapse). We randomly assigned participants (1:1) to receive either oral prednisone alone, 1·0 or 1·5 mg/kg per day tapered over 12 or 18 months (prednisone alone group), or 1000 mg of intravenous rituximab on days 0 and 14, and 500 mg at months 12 and 18, combined with a short-term prednisone regimen, 0·5 or 1·0 mg/kg per day tapered over 3 or 6 months (rituximab plus short-term prednisone group). Follow-up was for 3 years (study visits were scheduled weekly during the first month of the study, then monthly until month 24, then an additional visit at month 36). Treatment was assigned through central computer-generated randomisation, with stratification according to disease-severity (severe or moderate, based on Harman's criteria). The primary endpoint was the proportion of patients who achieved complete remission off-therapy at month 24 (intention-to-treat analysis). This study is registered withClinicalTrials.gov, numberNCT00784589 . Findings: Between May 10, 2010, and Dec 7, 2012, we enrolled 91 patients and randomly assigned 90 to treatment (90 were analysed; 1 patient withdrew consent before the random assignment). At month 24, 41 (89%) of 46 patients assigned to rituximab plus short-term prednisone were in complete remission off-therapy versus 15 (34%) of 44 assigned to prednisone alone (absolute difference 55 percentage points, 95% CI 38·4–71·7; p<0·0001. This difference corresponded to a relative risk of success of 2·61 (95% CI 1·71–3·99, p<0·0001), corresponding to 1·82 patients (95% CI 1·39–2·60) who would need to be treated with rituximab plus prednisone (rather than prednisone alone) for one additional success. No patient died during the study. More severe adverse events of grade 3–4 were reported in the prednisone-alone group (53 events in 29 patients; mean 1·20 [SD 1·25]) than in the rituximab plus prednisone group (27 events in 16 patients; mean 0·59 [1·15]; p=0·0021). The most common of these events in both groups were diabetes and endocrine disorder (11 [21%] with prednisone alone vs six [22%] with rituximab plus prednisone), myopathy (ten [19%] vs three [11%]), and bone disorders (five [9%] vs five [19%]). Interpretation: Data from our trial suggest that first-line use of rituximab plus short-term prednisone for patients with pemphigus is more effective than using prednisone alone, with fewer adverse events. Funding: French Ministry of Health, French Society of Dermatology, Roche.